Ultrafast lithium diffusion in bilayer buckled graphene: A comparative study of Li and Na. (15th March 2020) - Yamaletdinov, Ruslan D.; Pershin, Yuriy V.
Graphical abstract: Abstract: A spectacular enhancement of Li interlayer diffusion constant parallel to the folding axis is found. The ratio of the parallel to the perpendicular diffusion constant depends on the buckling direction and stacking, and increases with the degree of buckling. The strongest anisotropy is observed in the case of fixed zig-zag edges. A comparison with the diffusion of Na suggests that the strong asymmetry in the vibrational states of buckled graphene and also the smaller mass of Li are likely to contribute to the observed diffusion enhancement. This work opens a new pathway to develop highly-efficient anodes for rechargeable alkaline batteries.